Kualitas Semen Cair Kambing Peranakan Etawah dalam Modifikasi Pengencer Tris dengan Trehalosa dan Rafinosa (THE QUALITY OF ETAWAH CROSSBREED BUCK LIQUID SEMEN IN MODIFIED TRIS DILUENTS WITH TREHALOSE AND RAFFINOSE) - Ariantie, Oriza Savitri; Yusuf, Tuty Laswardi; Sajuthi, Dondin; Arifiantini, Raden Iis (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
The aim of this study was to compare the efficacy of trehalose and raffinose supplementation in Trisegg yolk (TEY) and Tris soya (TS) diluents in optimizing the quality of Etawah Crossbreed liquid semen.Semen were collected from three sexually mature bucks using artificial vagina. Semen were then evaluatedand divided into six aliquot tubes. Each of them was diluted in TEY and TS supplemented with 50 mMtrehalose or raffinose, respectively. The liquid semen were then stored in refrigerator (5°C). The motility,viability and plasma membrane integrity (PMI) of the spermatozoa were evaluated every 12 hours untilsperm motility remained up to 50%. The results showed that sperm motility in TEY supplemented withtrehalose or raffinose remained up to 50% for 72-84 hours, compared to in TS which was for 48-60 hours(P<0,05). The best diluent was demonstrated by TEY supplemented with trehalose where the spermmotility was 52,82±3,21% up to 84 h compared to raffinose supplementation (52,78±4,41%) and control(51,78±4,86%) which was up to 72 hours, respectively. Meanwhile, the spermatozoa motility in TS diluentsupplemented with raffinose was 52,78±4,41% for up to 60 hours compared to supplemented with trehalose(53,33±3,54%) and control (51,11±4,86%) which was up to 48 hours. In all diluents, the viability ofspermatozoa was 6-9% higher than the percentage of sperm motility, whilst the percentage of PMI wassimilar to the percentage of sperm motility. In conclusion, TEY supplemented with trehalose was the bestdiluents for preservation of Etawah Crossbreed buck liquid semen, and when using TS diluent it isrecommended to add raffinose  rather than trehalose.
Keywords: etawah crossbreed, liquid semen, tris egg yolk, tris soya, trehalose, raffinose